The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2583.2009.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced nitric oxide synthesis in the gut of Manduca sexta protects against oral infection by the bacterial pathogen Photorhabdus luminescens

Abstract: Injecting the insect pathogenic bacterium Photorhabdus luminescens into the blood system of the model lepidopteran insect Manduca sexta induces nitric oxide synthase (NOS) expression in the fat body and blood cells (haemocytes), whereas following oral ingestion of bacteria NOS expression is limited to the gut. We used RNA interference to knock-down expression of NOS throughout the insect. Preventing NOS induction in this way adversely affected the survival of orally infected insects and caused a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 69 publications
(98 reference statements)
3
27
0
3
Order By: Relevance
“…Bacterial challenge significantly increased SeNOS expression, indicating that SeNOS is an iNOS, as seen in other lepidopterans, including M. sexta [18] and B. mori [19].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bacterial challenge significantly increased SeNOS expression, indicating that SeNOS is an iNOS, as seen in other lepidopterans, including M. sexta [18] and B. mori [19].…”
Section: Discussionmentioning
confidence: 91%
“…More to the point, the inducible expression of NOS is site-specific to the foci of pathogen infection in M. sexta. Eleftherianos et al [18] demonstrated this by infecting hornworms with a bacterial pathogen, Photorhabdus luminescens, at different sites. M. sexta expressed NOS only in gut tissue following oral infection and only in the fat body and hemocytes following infection by hemocelic injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that although NO signalling emanates from a tissue other than blood cells it needs the latter to exercise its effect in the fat body (Djikers and O'Farrell, 2007). The guts of insects release NO (Foley and O'Farell, 2003;Eleftherianos et al, 2009), and following oral infection of Drosophila larvae with Ecc the gut is the tissue where bacteria activate dipt-GFP prior to fat-body expression and a systemic Journal of Cell Science 122 (24) Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…NOS (accession number (AN): AF062749) is induced in the midgut of Manduca sexta larvae fed with Photorhabdus luminescens. If the expression of NOS is knocked-down the survival of orally infected insects is affected and a significant increase in the number of bacteria crossing into the haemolymph was observed [6]. In Bombyx mori NOS is induced in the fat body by lipopolysaccharides [11].…”
Section: Introductionmentioning
confidence: 98%